Optical And Electrical Properties of PVA/A-Al2O3 Nanocomposite Films - El-Molla, Sara; Mahmoud, R.; Mansour, A.F.; Mansour, S.F.; Abdo, M.A. (JOURNAL OF ADVANCES IN PHYSICS, 2019)
In the present study, a-Al2O3 nanoparticles were synthesized using the citrate-nitrate auto combustion method. Nanocomposites of PVA/a-Al2O3 were intended by solution casting technique. The micrograph of samples were analysed by X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FESEM) and UV-visible spectroscopy analysis. UV-visible results showed that the direct optical band gap decreased with the increase of a-Al2O3 content. The refractive index has been dissected using Wemple and DiDomenico model. Hopping of charge carriers besides interfacial polarization could expound the demeanor of dielectric constant (E’), dielectric loss (E’’) and ac electrical conductivity (0-ac) with the frequency and temperatures.